Vitamin A deficiency in Bos indicus heifers fed a wheat straw diet cannot be corrected with algae lick blocks or intramuscular injectable retinyl palmitate treatments - Parker, A.J.; Goopy, John P.; Callaghan, M.J.; Vermunt, J.J.; Nys, R. de (Commonwealth Scientific and Industrial Research Organisation, 2017)
Serum and liver retinol concentrations and blood β-carotene concentrations were studied in 30 Bos indicus heifers rendered deficient of vitamin A over 180 days and then given treatments of access to algae-based lick blocks (n = 10), injectable retinyl palmitate and molasses-based lick blocks (n = 10), or a negative control given access to molasses-based lick blocks only (n = 10). All heifers became deficient in blood and liver vitamin A, as well as blood β-carotene by 180 days. There was no treatment effect on bodyweight (P = 0.347). However, a highly significant effect of time (P = 0.001) was detected where all heifers achieved an average daily gain of 0.74 kg/day throughout the depletion phase of the study but lost 0.150 kg/day during the repletion phase. The concentrations of serum and liver retinol and blood β-carotene were not different between treatment groups (P = 0.362, P = 0.535 and P = 0.839) during the depletion or repletion phases of the study. All heifers continued to be rendered deficient in the concentrations of serum and liver retinol and blood β-carotene throughout the experiment demonstrating a highly significant effect of time (P = 0.001). Injectable retinyl palmitate (818 100 IU retinol) or access to algal lick blocks (4180 IU retinol) did not elevate blood or liver retinol concentrations in heifers rendered deficient of vitamin A. It is speculated that the protein-deficient diet fed to the heifers had an adverse effect on the blood retinol transport proteins.